Comparing Macroeconomic Performance of the Union for the Mediterranean Countries Using Grey Relational Analysis and Multi-Dimensional Scaling - Onder, Emrah; Boz, Canser (European Scientific Journal, ESJ, 2017)
The aim of this study is to evaluate the economic performance of the Union for the Mediterranean (UfM) countries during 2006-2016 periods. The Union for the Mediterranean comprises the 28 EU Member States, the European Commission and 15 Mediterranean countries namely Albania, Austria, Bosnia and Herzegovina, Croatia, Czech Republic, Egypt, Finland, Germany, Hungary, Italy, Jordan, Lebanon, Luxemburg, Mauritania, Montenegro, The Netherlands, Poland, Romania, Slovenia, Sweden, Tunisia, United Kingdom, Algeria, Belgium, Bulgaria, Cyprus, Denmark, Estonia, France, Greece, Ireland, Israel, Latvia, Lithuania, Malta, Monaco, Morocco, Palestine, Portugal, Slovakia, Spain and Turkey. Syria has suspended its membership to the UfM on December 1, 2011. Libya has an observer status in the UfM. Grey Relational Analysis is used for the outranking of countries using macroeconomic indicators including total investment, gross national savings, inflation, average consumer prices, volume of imports of goods and services, volume of exports of goods and services, unemployment rate, general government revenue, general government total expenditure, general government gross debt, current account balance, gross product domestic (constant). Also annual macroeconomic indicators are converted to single data set by using arithmetic mean and weighted arithmetic mean (to be focused on recent years). This combined data was also used for another economic performance evaluation and Multidimensional Scaling Analysis has been used for weighted arithmetic mean to show countries’ positions relative to each other in a two-dimensional plane. The results of the empirical analyses show that Ireland ranked as first according to the weighted arithmetic mean among 36 UfM countries. Egypt and Tunisia have been found as the countries with the worst economic performance.